Temperature dependence of O2 respiration in mangrove leaves and roots: implications for seedling dispersal phenology. Issue 1 (11th October 2022) - Inoue, Tomomi; Akaji, Yasuaki; Baba, Shigeyuki; Noguchi, Ko
Summary: Seasonal differences in diaspore dispersal of three mangrove species, Kandelia obovata, Bruguiera gymnorrhiza and Rhizophora stylosa, suggest that respiratory energy production and demand may differ as a result of interspecific differences in temperature dependence of growth and maintenance processes during seedling establishment. We analyzed growth, temperature dependencies of respiratory O2 consumption and amounts of respiratory chain enzymes in seedlings of these species grown at various temperatures. Respiration rates measured at the low reference temperature, R REF, were highest in leaves of 15°C‐grown K. obovata, whose dispersal occurs in the cold season, while root R REF of 15°C‐grown R. stylosa was 60% those of the other species, possibly because of warm conditions during its establishment phase. In leaves and roots of K. obovata and leaves of R. stylosa, the overall activation energy, E o, changed with growth temperature associated with changes in the ratios of the amount of protein in the two respiratory pathways. However, E o of seedlings of B. gymnorrhiza, which has a long dispersal phase, were constant and independent of growth temperature. The different temperature responses of seedling respiration and growth among these three species may reflect the seasonal temperature range of seedling dispersal and establishment in each species.